Chronic pyloric hypertrophic gastropathy: Review - Zibetti, Francesca Lopes; Gonçalves da Silva, Eduardo; Rocha, Michaela Marques; Alves, Caroline Castagnara; Rosa, Brenda Madruga; Fernandes, Daniele Weber; Leão, Maysa Seibert de; Soares, Matheus de Azevedo; Vasconcellos, AmandaLealde; Costa, Paula Priscila Correia (Pubvet, 2021)
There are two forms of chronic pyloric hypertrophic gastropathy (GHPC), the first one being of congenital origin, which is the benign pyloric muscle hypertrophy, where the increase in cell volume occurs in the cells of the muscle layer; and the second one being acquired, which consists of hypertrophy of the mucosa of the gastric antrum, where this increase occurs in the mucous layer; both cause delayed gastric emptying as it results in stenosis of the pyloric lumen. This work aims to bring the literature review of both forms of GHPC. The definitive diagnosis of both is made from complementary imaging exams, especially endoscopy and biopsy; it’s very important to make the differential diagnosis for other diseases that present similar clinical signs, where the main one is vomiting right after the meal. The treatment of choice is surgical correction using the pyloroplasty technique, which requires monitoring the patient in the post-surgical period and the prognosis is usually favorable.